A study of customer satisfaction towards the service quality provded by IBS Technology Sdn. Bhd. / Ernna Edayu Dul Ngajis - Dul Ngajis, Ernna Edayu (Faculty of Business and Management, 2007)
This study is based on the research of 'A Study of Customer Satisfaction towards the services provided by IBS Technology'. The questionnaires have been distributed 31 respondents from 11 companies who have used the services from IBS Technology. Most of the companies have been used for these services about 1 to 3 years operations. In this study researcher had done the research of identifying the level of customer satisfaction with the service quality of IBS Technology management. Service qualities in this study refer to the staffs' performance from 3 departments which are Business Development Department, Project Management Department, and Maintenance Department.